A Multidisciplinary Approach to Managing Diabetes Complications: Integrating Internal Medicine, General Practice, Nursing, Physiotherapy, and Dentistry to Improve Patient Clinical Outcomes - Albalawi, Ahmed Mohammed; Alghamdi, Mohammed Abdullah; Alquaymi, Sarah Mubarak Abdullah; Thubab, Hassan Mohammed Abdullah; Alsanie, Ahmad; Al-Sharif, Israa Shaker Hassan; Almagali, Rahaf Ahmed Ali; Attllah, Wed Morad Ahmad (Journal of Ecohumanism, 2025)
Diabetes mellitus is a chronic, progressive metabolic disorder characterized by persistent hyperglycemia and multisystem involvement. The disease is associated with substantial microvascular, macrovascular, neuromuscular, and periodontal complications that significantly impair quality of life and increase healthcare expenditure. Despite advancements in pharmacotherapy, complication rates remain high, reflecting limitations in fragmented care delivery models. Contemporary evidence increasingly supports multidisciplinary, patient-centered approaches as superior frameworks for managing diabetes and its associated complications. This comprehensive literature review critically examines the integration of Internal Medicine, General Practice, Nursing, Physiotherapy, and Dentistry in the management of diabetes complications. The review synthesizes pathophysiological mechanisms, epidemiological data, discipline-specific contributions, collaborative care frameworks, economic implications, psychosocial determinants, digital health integration, and implementation challenges. Evidence demonstrates that structured multidisciplinary models significantly improve glycemic control, reduce cardiovascular events, enhance functional mobility, decrease hospitalizations, improve periodontal health, and optimize long-term patient outcomes. The findings underscore the necessity of integrated healthcare systems to address the systemic complexity of diabetes and support sustainable improvements in clinical outcomes.